Pengaruh Penambahan Tepung Serai Wangi (Cymbopogon nardus L.) sebagai Imbuhan Pakan dalam Ransum terhadap Performa Ayam Jowo Super (Joper) - Zaidan, Muhammad Nahar; Sudrajat, Deden; Kardaya, Dede (Universitas Djuanda, 2024)
Ayam Joper stands for Ayam Jowo Super or often known by the public as Ayam Kampung Super. Joper chicken is the result of a cross-breed between male native chickens and laying hens. The Citronella plant is a type of plant from the grass family with bioactive substances, namely essential oils, citronella, geraniol, citral, eugenol, cadine, and cadinol which have the potential to become feed additives. The purpose of this study was to examine the effect of the addition of citronella meal (Cymbopogon nardus L.) as a feed additive in the ration on the performance of Joper. This research was conducted for 63 days from July 26 to September 26, 2023, located in Padasuka Village, Ciomas, Bogor. This study used Joper chickens with an average initial body weight of 34.9 ± 2.71 grams. The design model used in this study is a completely randomized design (CRD) consisting of 5 treatments 4 replicates, each replicate has 5 Joper chickens. The treatments given were R0 = basic ration without the addition of 0% citronella meal, R1 = basic ration with the addition of 2% citronella meal, R2 = basic ration with the addition of 4% citronella meal, R3 = basic ration with the addition of 6% citronella meal, R4 = basic ration with the addition of 8% citronella meal. The results showed that the addition of citronella meal as a feed additive in the ration had an effect (P<0.05) on increasing ration consumption, maintaining body weight gain, and reducing the feed conversion ratio of Joper chickens. The conclusion of this study is the addition of citronella meal in a ration of as much as 6% gives the best results on ration consumption and body weight gain while the addition of citronella meal in the ration as much as 8% the best result on feed conversion ration in week 3 and 7.